1970
DOI: 10.1042/bj1170951
|View full text |Cite
|
Sign up to set email alerts
|

The function of subcellular fractions in the oxidation of glutathione in rat liver homogenate

P. C. Jocelyn

Abstract: 1. The aerobic loss of GSH added to the supernatant fraction from rat liver is much increased by including the microsome fraction, which both inhibits the concurrent reduction of the GSSG formed and also augments the net oxidation rate. 2. Oxidation occurs with a mixture of dialysed supernatant and a protein-free filtrate; the latter is replaceable by hypoxanthine and the former by xanthine oxidase, whereas fractions lacking this enzyme give no oxidation. 3. In all these instances augmentation occurs with micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…1 gives representative data). Studies with external GSH levels of 20-30 mM gave variable results, and equilibrium was reached at 5 min or later; such levels of GSH, which are not physiological, have been reported to cause mitochondrial damage (32,33). Uptake of GSH at 40C was slower than at 230C, but the equilibrium values were higher because GSH efflux (see below) was very slow at 40C.…”
Section: Resultsmentioning
confidence: 97%
“…1 gives representative data). Studies with external GSH levels of 20-30 mM gave variable results, and equilibrium was reached at 5 min or later; such levels of GSH, which are not physiological, have been reported to cause mitochondrial damage (32,33). Uptake of GSH at 40C was slower than at 230C, but the equilibrium values were higher because GSH efflux (see below) was very slow at 40C.…”
Section: Resultsmentioning
confidence: 97%
“…GSH-Px tarafından katalizlenen reaksiyonda GSH'nın H2O2 ile oksidasyonu sonucu oluşan GSSG'nin glutatyon redüktaz (GSSG-Rd) kataliziyle tekrar GSH'a dönüşmesi sırasında tüketilen NADPH konsantrasyonu üzerinden 340 nm'de oluşan absorbans azalmasının 4 dakika boyunca izlenmesi prensibine dayanır (Jocelyn., 1970).…”
Section: Gpx Enzim Aktivitesinin öLçümüunclassified
“…This en7yme shows high specificity in the oxidation of the purines hypoxanthine and .ranthine but can also oxidize a wide variety of substrates that belong to many classes of compounds.10 These substrates include sulfur-containing compounds, such as sulfite," glutathione, and other thiols. [12][13][14] Due to these considerations, the effect of xanthine oxidase on diethyldithiocarbamate was tested in vitro. During these investigations, a new color reaction between diethyldithiocarbamate and nitro blue tetrazolium was found that was developed into a simple quantitative assay for compound I.…”
mentioning
confidence: 99%